Effect of Liquid Nitrogen Freezing on Maintaining the Quality of Crayfish During Freeze–Thaw Cycles: Muscle Structure and Myofibrillar Proteins Properties - Zongna Teng; Xiaoyue He; Liuqing Wang; Limin Xu; Chuyi Jiao; Jiwang Chen (Foods)
The quality of frozen crayfish (Procambarus clarkii) is challenged by freeze–thaw (FT) cycles during storage. The effect of freezing methods on the quality of crayfish during FT cycles was investigated by comparing physicochemical properties, microstructure, and myofibrillar protein (MPs) properties. Three methods were used for crayfish freezing, including air convective freezing (AF) at −20 °C and −50 °C, as well as liquid nitrogen freezing (LNF) at −80 °C. The frozen crayfish were thawed at 4 °C after 45 d of frozen storage as 1 FT cycle. After 5 FT cycles, the water holding capacity of LNF crayfish (70.8%) was significantly (p < 0.05) higher than that of −20 °C AF crayfish (60.6%) and −50 °C AF crayfish (63.5%). The drip loss of LNF crayfish (7.83%) was significantly lower than that of AF crayfish. Moreover, LNF maintained the gel strength and the thermal stability of MPs from crayfish with higher gel storage modulus and enthalpy. These results demonstrated that LNF minimized the formation of large ice crystals, preserving the structural integrity of muscle and the properties of MPs, thereby maintaining crayfish quality. This study investigated the effect of LNF in preserving crayfish quality during FT cycles, providing valuable insights for reducing the quality degradation of aquatic products during storage and transportation.